Properties of cement sand brick containing ground palm oil fuel ash (POFA) as partial sand replacement - Muhammad Azreen, Ibrahim (2017)
Cement sand brick is a type of brick made from a mixture of cement and sand. Due to growth of construction industry in Malaysia, demand toward construction material such as sand will increase. Uncontrollable usage of sand will lead to increase in river sand mining activity that can cause ecological imbalance such as destruction of flora and fauna, river bank erosion and water pollution. Palm Oil Fuel Ash (POFA) is a solid waste from burning palm oil husk and palm oil shell in the boiler of palm oil mill that is usually dumped at landfill. By replacing sand with POFA, sand mining and waste disposal problems can be reduced as well as economical cement sand brick can be produce. This research aims to investigate the effect of ground POFA as partial sand replacement on the properties of cement sand brick. The field of studies also covers important parameters including compressive strength, flexural strength, and water absorption in determining the engineering properties. All the specimen were subjected to air curing. The compressive and flexural strength tests have been conducted on 7, 14, 28 and 60 days. Water absorption were conducted at the age 28 days. Based on result, the compressive and flexural strength of the brick exhibit the same trend. Finding shows that cement sand brick containing 15% of ground POFA replacement give the best results in terms of highest compressive strength and flexural strength. The strength started to increase strength at 5% of POFA replacement until it achieve highest strength at 15%. Then it start to decrease when POFA replacement at 20%. Cement sand brick containing 15% POFA exhibit the lowest water absorption